Shelf-life prediction of micro-encapsulated shrimp oil in different packages using empirical models - Takeungwongtrakul, Sirima; Benjakul, Soottawat; Pisuchpen, Supachai; Kaewthong, Pensiri; Nalinanon, Sitthipong (My University, 2020)
Micro-encapsulated shrimp oil (MSO) can be used to fortify food products and may be especially useful in the development of new functional foods. The shelf-life of packaged MSO was studied and sorption isotherms were examined. Moisture sorption isotherms and moisture sorption kinetics of MSO were evaluated at 30°C for water activity (aw) values ranging from 0.113 to 0.923 by a static gravimetric method. Empirical models were determined to predict the experimental data. The initial stage of moisture sorption by the MSO was relatively rapid and it decreased with time. All the sorption curves were found to be type III. The most suitable model for predicting the moisture sorption isotherm of MSO was the GAB model because it had the lowest percentage root mean square error (RMSE). The shelf-life of MSO packaged in polypropylene (PP), Nylon/linear low density polyethylene (Nylon/LLDPE) and metalized polyethylene terephthalate (metalized PET) pouches stored at 30°C and either 75% or 80% relative humidity (RH) was predicted by the GAB equation and the longest shelf-life of MSO (507 days in 80% RH and 725 days in 75% RH) was found in metalized PET packages. The empirical models can be useful for predicting the shelf-life of MSO.
Keywords: Empirical model; Micro-encapsulated shrimp oil; Moisture sorption isotherm; Packaging; Shelf-life